ANALISIS FUNGSI TARI BUKONG DALAM UPACARA ADAT KEMATIAN DAYAK PESAGUAN DI DESA SERENGKAH KECAMATAN TUMBANG TITI KABUPATEN KETAPANG - Apriani, Nadella; Istiandini, Winda; Tindarika, Regaria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The traditional death ceremony in Serengkah village Tumbang Titi district, Ketapang regency has several processes that have existed since ancient times, in this traditional death ceremony there is a dance which is commonly called the Bukong Dance. The general objective of this research is to describe the process of carrying out traditional funeral ceremonies in Serengkah Village, Tumbang Titi District Ketapang Regency. Describe the function of the Bukong dance in the traditional ceremony of death in Serengkah Village, Tumbang Titi District Ketapang Regency. The method used in this study is a descriptive method with a qualitative research form, and an anthropological approach. The data contained in this study are facts regarding the ritual process carried out at the time of the traditional death ceremony owned by the Dayak Pesaguan tribe. The data were analyzed qualitatively with Mr. Napolino, Mr. Alipius, and Mr. Khajri who know clearly about the Bukong dance. The data through the results of observation, interviews, and documentation.